Akad Nikah Daring (Studi Kasus Akad Nikah Shaffira Gayatri dan Max Walden) - Karyono, Quoies Hassan (UNES Law Review, 2023)
This research aims to examine the phenomenon of online marriage contracts from two main perspectives: Islamic law and a phenomenological approach. Fundamental questions arise along with these developments. What is the practice of carrying out online marriages and what is the view of Islamic law regarding the validity of marriage contracts carried out online. This research will explore this problem by using a phenomenological approach to understand the social and normative impacts of online marriage contract practices. In addition, this research will also involve an analysis of Islamic legal views related to this practice, considering the importance of marriage in the teachings of the Islamic religion. The case study of Fira and Max Walden's marriage illustrates how technology has facilitated long-distance relationships and allowed couples to overcome geographic barriers. However, it is important to remember that the implementation of an online marriage contract must comply with the legal requirements stipulated in Islamic law, such as ittihād al-majelis, lafadz yang sharih, and ittisāl, as stipulated in the MUI fatwa. Thus, this practice can be recognized as valid in the view of Islamic law if it meets the stipulated conditions.